Study of farm machinery power and total operating cost in paddy field Sungai Balang, Johor / Nur Najwa Ab Ghafar - Ab Ghafar, Nur Najwa (Faculty of Plantation and Agrotechnology, 2018)
Rice (Oryza sativa) is one of our staple food in the worldwide and have a large number of consumers. Most of rice producer are using agricultural practices. Mechanization is combination application of mechanical that apply at farm and it need utilization, maintenance and repair the tools, equipment and also costing. Farm mechanization usage with suitable engine power and specialized equipment affected on cost of paddy rice production and mechanization cost. To determine the relationship between mechanization and management cost besides comparing actual Field Efficiency and theoretical Field Efficiency, secondary data was taken at paddy field in Sungai Balang, Johor. Two different types of machine data was taken that are tractor Kubota M9540 with 95 horsepower and combine harvester New Holland 1545 with 150 horsepower. Total area of study, total time taken, speed, width of mechanization implement, farm mechanization cost, and power usage was measure to calculate by using formula Theoretical Field Capacity (TFC), Effective Field Capacity (EFC), Field Efficiency (FE), fixed cost, and operation cost. Fixed cost calculation on tractor are half from total cost and the highest rate that are 47% because less budget to repair and maintenance are needed while fuel and lubricant cost of combine harvester is the most higher from total cost which are 41%. Higher fuel and lubricant cost in using combine harvester because more time losses during operating the harvester in field. High annual usage make combine harvester need more repair such as engine overhaul, routine and accidental breakage. Tractor’s FE is higher than combine harvester’s FE that are 83.52% and 56.81% because of higher EFC. Effect of high difference between actual FE and theoretical FE on combine harvester is higher operating cost and lower fixed cost while small differences between actual FE and theoretical FE on tractor make lower operating cost and higher fixed cost.